2021
DOI: 10.3892/etm.2021.10049
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone mineral density, 25‑hydroxyvitamin D3 and inflammatory factors in patients with hyperthyroidism

Abstract: The present study aimed to evaluate changes in bone mineral density, 25-hydroxyvitamin D 3 [25-(OH)D 3 ] and inflammatory factors in patients with hyperthyroidism, in order to determine the correlations with the pathogenesis of hyperthyroidism. A total of 55 patients with hyperthyroidism (observation group) and 53 healthy patients (control group) enrolled at Weifang People's Hospital from March 2017 to February 2018 were randomly enrolled. The thyroid function, bone mineral density, 25-(OH)D 3 and inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Therefore, 25(OH)D deficiency was previously found to be closely related to both hyperthyroidism and hypothyroidism. 25 , 26 Consistent with these findings, we also found that both hyperthyroidism and hypothyroidism were significantly associated with 25(OH)D deficiency in postmenopausal women with T2DM.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, 25(OH)D deficiency was previously found to be closely related to both hyperthyroidism and hypothyroidism. 25 , 26 Consistent with these findings, we also found that both hyperthyroidism and hypothyroidism were significantly associated with 25(OH)D deficiency in postmenopausal women with T2DM.…”
Section: Discussionsupporting
confidence: 85%